Identification of oxidative stress-responsive genes in recurrent miscarriage and their role in disease pathogenesis - Mian Wang; Lingling Zhu; Xiaoyan Cheng (PLoS ONE, 2025)
Recurrent miscarriage (RM) is a distressing reproductive condition affecting approximately 1–3% of couples. The underlying causes related to oxidative stress remain largely unclear and necessitate additional research. This study aimed to employ bioinformatics approaches to uncover the differential expression of oxidative stress-responsive genes in RM to elucidate their potential involvement in the disorder etiology. Upon examination of the data retrieved from the Gene Expression Omnibus (GEO), 18 oxidative stress-responsive differentially expressed genes (OSRDEGs) were identified. Bioinformatics techniques, which led to the identification of six hub genes— ARRB2 , BMF , SORCS2 , STK3 , UCN2 , and VIPR1 —as potential biomarkers for RM, elucidated the biological processes and molecular functions associated with genes that are differentially expressed under oxidative stress. GSEA enrichment profiling revealed significant enrichment of genes between the RM and control groups in pathways such as hypoxia, epithelial‒mesenchymal transition (EMT) in breast tumors, upregulation of Wnt signaling in liver cancer progenitors, and TGFβ-induced EMT. The mRNA-miRNA interaction network analysis revealed five hub genes interacting with 41 miRNAs, with STK3 exhibiting the highest connectivity among miRNA interactions. Additionally, the analysis of immune cell infiltration demonstrated a substantial inverse relationship between ARRB2 and the levels of plasma cells and neutrophils. Conversely, UCN2 was positively associated with T. cells. CD8 are inversely associated with monocytes. Furthermore, immunohistochemical (IHC) analysis on endometrial tissues from RM patients and matched controls confirmed significantly elevated protein expression levels of six hub genes in the RM group, consistent with the bioinformatics findings. This study establishes a diagnostic model and provides insights into immune-modulation therapies for RM.